Umbrella sampling of proton transfer in a creatine-water system - Ivchenko, Olga; Bachert, Peter; Imhof, Petra (Chemical Physics Letters, 2014)
Proton transfer reactions are among the most common processes in chemistry and biology. Proton transfer between creatine and surrounding solvent water is underlying the chemical exchange saturation transfer used as a contrast in magnetic resonance imaging. The free energy barrier, determined by first-principles umbrella sampling simulations (EaDFT 3 kcal/mol) is in the same order of magnitude as the experimentally obtained activation energy. The underlying mechanism is a first proton transfer from the guanidinium group to the water pool, followed by a second transition where a proton is "transferred back" from the nearest water molecule to the deprotonated nitrogen atom of creatine. © 2014 The Authors.
CRIS-Team Scopus Importer:2020-02-18